To Compare Serum Procalcitonin And CRP As Markers Of Neonatal Sepsis - Rafiq Ahmad; Israr Liaquat; Nadia Mumtaz; Sughra Zulfiqar; Sidra tul Muntaha; Nazia Rafique (Journal of Rawalpindi Medical College)
Objective: This study compares serum Procalcitonin (PCT) levels with CRP as predictive markers for neonatal sepsis.